(3ebOeI aj GdSjGSGJ GdYGeI GdebGQfI (B:s (3SjGSGJ GdNOeI GdeOfjI (B/s - (3YhOI, LgGO MQHs ((3GdbGgQI (B:s (3GdecJH GdYQHj ddeYGQa,s, 2017)
(3jJfGhd cJGH (B((3ebOeI aj GdSjGSGJ GdYGeI GdebGQfI (B: (3SjGSGJ GdNOeI GdeOfjI(B) (3hGdPj bGe HJCdjag (B((3LgGO YhOI(B) (3aj MhGdj (B(752) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdNOeI GdeOfjI, GdSjGSI GdYGeI(B) (3; gPG GdcJGH jbOe feW SGOS ai CfeGW dCReGJ GdGSJQGJLjg(B. (3aaj cJGH JbOjQ GdCReGJ GdGSJQGJLjg ai GdYGde GdYQHj Je JbOje CQHYg CfeGW hgj (B: 1-(3CReg Gdghjg GdGSJQGJLjg, (B2-(3CReg HfGA bhg GSJQGJLjg, (B3-(3CReg GJUGd GSJQGJLi, (B4-(3CReg ehGQO GSJQGJLjg(B.s
(3QShe GdZdGa (B: (3TQja GdZGdj(B.s
Keywords: (3GdNOeI GdeOfjIs; (3GdSjGSI GdYGeIs